The Timing and Strength of Regional Brain Activation Associated with Word Recognition in Children with Reading Difficulties - Rezaie, Roozbeh; Simos, Panagiotis G.; Fletcher, Jack M.; Juranek, Jenifer; Cirino, Paul T.; Li, Zhimin; Passaro, Antony D.; Papanicolaou, Andrew C. (Frontiers in Human Neuroscience, 2011)
The study investigates the relative degree and timing of cortical activation across parietal, temporal, and frontal regions during performance of a continuous visual word recognition task in children who experience reading difficulties (N=44, RD) and typical readers (N=40, NI). Minimum norm estimates of regional neurophysiological activity were obtained from magnetoencephalographic recordings. Children with RD showed bilaterally reduced neurophysiological activity in the superior and middle temporal gyri, and increased activity in rostral middle frontal and ventral occipitotemporal cortices, bilaterally. The temporal profile of activity in the RD group, featured near-simultaneous activity peaks in temporal, inferior parietal and prefrontal regions, in contrast to a clear temporal progression of activity among these areas in the NI group. These results replicate and extend previous MEG and fMRI results demonstrating atypical, latency-dependent attributes of the brain circuit involved in word reading in children with reading difficulties.